2015
DOI: 10.3748/wjg.v21.i32.9614
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of acute-on-chronic liver failure patients treated with artificial liver support system

Abstract: A novel model was constructed to predict prognosis and accurately discriminate survival in ACLF patients treated with an artificial liver support system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…Pre-existent research showed that ALT and AST show not correlation with the severity or prognosis of HBV-related ACLF and prophase HBV-related liver failure. [ 28 30 ] In the present research, ALT and AST were also not independent influencing factors of ACLF occurrence in patients with AD of HBV-related CLD. ALT and AST rapidly and easily decreased, which was observed by clinicians because of the medical treatment given to patients and the bilirubin–enzyme separation phenomenon.…”
Section: Discussioncontrasting
confidence: 57%
“…Pre-existent research showed that ALT and AST show not correlation with the severity or prognosis of HBV-related ACLF and prophase HBV-related liver failure. [ 28 30 ] In the present research, ALT and AST were also not independent influencing factors of ACLF occurrence in patients with AD of HBV-related CLD. ALT and AST rapidly and easily decreased, which was observed by clinicians because of the medical treatment given to patients and the bilirubin–enzyme separation phenomenon.…”
Section: Discussioncontrasting
confidence: 57%
“…PE has been widely used in China due to its ability to rapidly remove over‐accumulated toxic materials and replace beneficial plasma substances . Although PE alone is useful, combining PE with other purification methods is even more effective . It was reported that if MELD score could be reduced prior LT, the prognosis of HBV‐ACLF could be improved .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the dose was usually set to one total plasma volume, which was approximately 5% of body weight (approximately 3,000 mL) [ 22 ]. Due to the shortage of plasma in recent years and a retrospective study suggesting that plasma adsorption plus PE therapy could reduce the amount of plasma needed for PE therapy without impairing the therapeutic efficiency [ 23 ], plasma adsorption plus PE with half the total plasma volume (approximately 1,500 mL) is now widely used for ALSS therapy in China.…”
Section: Methodsmentioning
confidence: 99%